Effect of daily thinning on biweekly increment of growth and yield of maize (Zea mays L.) in mountainous agroecosystem - Muhammad Arshad; Rab Nawaz; Sajjad Ahmad; Muhammad Atif Irshad; Ali Irfan; Mir Muhammad Nasir Qayyum; Khalid S. Almaary; Muhammad Afzaal; Zulkfil Ahmed; Mohammed Bourhia (BMC Plant Biology)
Abstract Maize (Zea mays L.) growth and yield are severely affected due to intraspecific competition and agroclimatic conditions when cultivated with high plant densities. Field trials comprising four daily thinning patterns (0, 0.5, 1.0, &1.5% till silking) carried out in three consecutive years (2019–2021) using RCBD experimental design consisting of three replicates. Growth variables, dry matter allocation and growth rates in maize were examined during five biweekly periods starting from the emergence (15, 30, 45, 60 and 75 days after emergence, DAE) till silking whereas yield parameters i.e., biological yield, economic yield, and sustainability yield index (SYI) were recorded. Biweekly increase in growth variables, dry matter partitioning and growth rates of maize differed significantly due to the influence of daily thinning computed for the periods from 31 to 45, 46 to 60 and 61 to 75 DAE but the same parameters didn’t differ significantly during the first two biweekly periods (1–15 & 16–30 DAE). Increase in growth variables, dry matter distribution, absolute growth rate (AGR), yield and SYI was the greatest where maize was established with 1% daily thinning. This increase in growth and dry matter partition observed highly associated to economic yield and biological yield. Current research highlighted that 3, 4th, and 5th biweekly periods are the most critical stages and daily thinning of 1% is suggested for higher and sustainable economic and biological returns from high density broadcasted maize.